An Evaluation of CNN and SVM Algorithms for Facial Recognition - Pooja P. Raj; Dr. Amrita Verma (International Journal of Machine Systems and Manufacturing Technology, 2024)
With the use of facial recognition technology, someone's identity can be confirmed or identified. Real-time or picture-based facial recognition technology can be used to identify individuals. One of the most important elements in the field of biometric security is facial recognition. The technology is mostly used in the fields of law enforcement and defence, while interest in other fields is growing. To recognize the face, numerous technologies and algorithms were developed and used. In this paper, we will study two algorithms that are CNN and SVM for detecting face and analysis the best algorithm between the two. This work is organized into sections: an introduction, a face detection methods section, face detection using algorithms, and a result and conclusion section
Keywords: CNN; Face detection; Landmark; SVM; dlib